Obesity and the dysregulation of fatty acid metabolism: implications for healthy aging. Issue 6 (1st November 2016) - Morgan, Amy; Mooney, Kathleen; Mc Auley, Mark.
ABSTRACT: Introduction: The population of the world is aging. In 2010, an estimated 524 million people were aged 65 years or older representing eight percent of the global population. By 2050, this number is expected to nearly triple to approximately 1.5 billion, 16 percent of the world's population. Although people are living longer, the quality of their lives are often compromised due to ill-health. Areas covered: Of the conditions which compromise health as we age, obesity is at the forefront. Over half of the global older population were overweight or obese in 2010, significantly increasing the risk of a range of metabolic diseases. Although, it is well recognised excessive calorie intake is a fundamental driver of adipose tissue dysfunction, the relationship between obesity; intrinsic aging; and fat metabolism is less understood. In this review we discuss the intersection between obesity, aging and the factors which contribute to the dysregulation of whole-body fat metabolism. Expert commentary: Being obese disrupts an array of physiological systems and there is significant crosstalk among these. Moreover it is imperative to acknowledge the contribution intrinsic aging makes to the dysregulation of these systems and the onset of disease.